Peningkatan Kinerja Guru dalam Pembelajaran Melalui Pola Kepemimpinan Transformasional Kepala Sekolah di SMP Santu Fransiskus Xaverius Ruteng, Kabupaten Manggarai - Fredrikus Djelahu Maigahoaku (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
The aim of this study is to improve the science of school based management interest and outcomes using a Transformational Leadership model to manage the performance of teachers on school. This study was done at a secondary school SMP St. FransiskusXaveriusRuteng in Manggarai regency. The kind ofthis study is an action research in school and were done in two circle of acts. This study involved the principal, the teachers, and some students as informant and participant. The data collecting techniques were interview, observation, questioners, and document study.The results of the study have shown that before the transformational leadership wasapplied, there were 52,65% low performance teachers in pedagogic, professional, personality, and social ability. Daily routine activity with no creativity and innovationwere found as the roots main problems and also the weakness of principal leadership. On the first circle actions there were four actions as the solutions to overcome the problem; 1) teacher self-evaluation, 2) application of transformational leadership, 3) strengths capacity and capability of teaching and learning, and 4) peer evaluation for teachers.On the second circle the actions were focused on communication and human relationships among the teacher and their principal. The solutions were conducted by the principal through a transformational leadership model; 1) idealized influence, 2) intellectual stimulation, 3) inspirational motivation, 4) charisma, and 5) individual consideration. The results of applying transformational leadership model were the increase of teacher performance on pedagogic; on the first circle 78,90% and on the second circle 84,20%. Performance on professional on the first circle 77,60% and on the second circle 83,30%. Performance on personality; on the first circle 77,70% and on the second circle 83,20%. Performance on social; on the first circle 77,80% and on the second circle 83,70%.The results recommend the principal of secondary school SMP St. Fransiskus Xaverius Ruteng toapply the transformational leadership model to conduct some activities on the school life and would improve the teacher performance.